From re-instrumenting to re-purposing farm support policies - Anderson, Kym; Strutt, Anna (International Food Policy Research Institute, 2023)
The world’s agrifood systems have served society well since 1798 when Malthus anonymously published An Essay on the Principle of Population. That is especially so since the 1950s, when famines became a thing of the past except where deliberately contrived by a country’s leaders or rebels for local political purposes (Ravallion 1987, 1997). Yet global food supplies have not been produced very efficiently, equitably or sustainably, especially during the past seven decades. Nor has food been consumed so as to optimize individuals’ nutrition and health. Institutions and policies have contributed to this unsatisfactory outcome, particularly insofar as they distort incentives facing producers and consumers, and thereby dampen investor incentives. Moreover, numerous communities are calling out for a major overhaul of agrifood systems and policies, demanding among other things that they do more to improve nutrition and human health and ease natural resource and environmental stresses, particularly in the face of changing climates (United Nations 2021; Gautam et al. 2022; FAO et al. 2022).